2005
DOI: 10.1126/science.1117542
|View full text |Cite
|
Sign up to set email alerts
|

Crossing the Termination Shock into the Heliosheath: Magnetic Fields

Abstract: Magnetic fields measured by Voyager 1 show that the spacecraft crossed or was crossed by the termination shock on about 16 December 2004 at 94.0 astronomical units. An estimate of the compression ratio of the magnetic field strength B (+/- standard error of the mean) across the shock is B2/B1 = 3.05 +/- 0.04, but ratios in the range from 2 to 4 are admissible. The average B in the heliosheath from day 1 through day 110 of 2005 was 0.136 +/- 0.035 nanoteslas, approximately 4.2 times that predicted by Parker's m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
150
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 220 publications
(168 citation statements)
references
References 24 publications
16
150
1
1
Order By: Relevance
“…(5). These choices of s(θ) are in accordance with the compression ratio observations made by V1 and V2, ranging from s = 3 ± 1 (Burlaga et al 2005) to s = 2.4 (Richardson et al 2008). This transition is again shown in the top panel of Fig.…”
Section: The Modulation Modelsupporting
confidence: 59%
“…(5). These choices of s(θ) are in accordance with the compression ratio observations made by V1 and V2, ranging from s = 3 ± 1 (Burlaga et al 2005) to s = 2.4 (Richardson et al 2008). This transition is again shown in the top panel of Fig.…”
Section: The Modulation Modelsupporting
confidence: 59%
“…The bulk speed V in the heliosheath [Richardson and Wang, 2010], observed by the plasma instrument on V2 [Bridge et al, 1977], has been twice as high as that observed by Voyager 1 (V1) when it crossed TS in December, 2004 [Stone et al, 2005;Gurnett and Kurth, 2005;Decker et al, 2005;Burlaga et al, 2005a]. These high speeds were observed from the last crossing of the TS in September 1, 2007September 1, (2007 to 2009.7.…”
Section: Introductionmentioning
confidence: 64%
“…[2] The 23 September issue of Science documented the Voyager 1 spacecraft's recent and remarkable crossing of the heliospheric Termination Shock (TS) [Stone et al, 2005;Decker et al, 2005;Gurnett and Kurth, 2005;Burlaga et al, 2005], the innermost structure in our heliosphere's interaction with the local interstellar medium. The TS marks the boundary where the Sun's supermagnetosonically expanding solar wind abruptly slows to become sub-magnetosonic flow.…”
Section: Introductionmentioning
confidence: 99%
“…[4] On 16 December 2004, the Voyager 1 spacecraft crossed the termination shock at a heliocentric distance of $94 AU, directly measuring the expected compression of magnetic field [Burlaga et al, 2005] inferring strong slowing of the solar wind [Decker et al, 2005], and observing the end of upstream plasma oscillations [Gurnett and Kurth, 2005]. The shock was also a steady source of lower energy energetic protons [Stone et al, 2005] and the lowest energy electrons and ions exhibited roughly ten-fold increases across the shock, with smaller increases at higher energies [Decker et al, 2005].…”
Section: Introductionmentioning
confidence: 99%